Can social pensions for the elderly mitigate shocks? Lessons from Mozambique - Sara Almeida; Hanna Berkel; Sam Jones; Patricia Justino; Telça Massingue; Hilário Muchabel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study investigates the contribution of Mozambique's flagship social pension programme, the Programa de Subsídio Social Básico, to building resilience against shocks. Applying a fuzzy regression discontinuity approach to bespoke survey data, we separate direct effects of programme transfers from anticipation effects related to becoming programme-eligible. Our results show that while eligibility is associated with adopting more positive coping strategies, the impact of transfers is mixed. Specifically, we find that transfers made close in time to major climate shocks offer some short-term benefits. However, we demonstrate that increasingly acute operational challenges, including extended delays in receiving payments, have materially weakened household resilience. Complementary analysis of nationally representative household budget data confirms that programme transfers support significant consumption gains, but these fade within around six months. These findings highlight the critical importance of timely payments and reliable 'last mile' administration to fulfil the programme's potential for effectively supporting vulnerable populations exposed to shocks.
Keywords: H53; I38; Q54; 330; social protection; elderly; pensions; fuzzy regression discontinuity; Mozambique